(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2019)
Along these lines, we will address two initiatives carried out at the Universidad Nacional del Sur (National University of the South) aimed at establishing permanent channels of dialogue with the community of which we are part. These are intended to consolidate a virtuous circle of feedback that strengthens teaching, extension and research. The experiences presented are framed within a particular conception of the public university and of the university extension itself. Likewise, they correspond to a history and institutional development whose knowledge is transcendental to understand its current state. Hence, in these brief reflections, we will try to retrace those concepts and that chronology.